Condicionantes do crescimento dos fundos mútuos de investimento no Brasil e no Peru: um estudo das captações líquidas agregadas - Robert Aldo Iquiapaza Coaguila (2005)
The mutual funds (MFs) are institutional investors that promote the development of capital markets through the liquidity of securities and transparency of the companies, offering advantages of portfolio diversification, especially to small investors. The objectives of thisresearch were: to determine the net flows (NFs) of money for MFs in Brazil and Peru, to determine the importance of NFs in the growth of the net assets (NA), and to identify the determinants of the development of MFs through the study of aggregate NFs. The period of study was February 1995 - September 2004 in Brazil, and February 1996 December 2004 in Peru. The categories analyzed were, in Brazil: stock funds, exchange rate, referenced in deposits overnight and money market, balanced and bond funds; and in Peru: balanced funds, bond funds-nuevos soles and bond fundsdollars. A simulation study allowed to identify a better form of estimate NFs when daily information is not available, this differs from the traditional way by considering an average net asset value in the calculation a and not only the final value. The analysis of aggregate NFs since the beginning of the study period revealed that in some cases NFs represent up to 100% or more of NA indicating that in those periods the growth of the funds was explained more by the investor's money that went into funds than for the accumulated capital gains. The explanatory variables were those from theoretical and/or empiric studies, available for investors or being feasible estimated starting from known information. For the third objective, the data were analyzed by multiple regressions with monthly series, where the accumulated NFs of each category were the dependent variable. In search of robustness, classic estimators were compared with constrained CM-estimators. The significant determinants were: besides the return of the own funds; the investors income, using the growth in GNP per capita as a proxy, both in the contemporary or lagged periods;the smallest interest rates; and the least volatility or market risk. Changes in the regulation, like the introduction of valuation at market prices for fixed income securities, passed up by the two countries, in circumstances of national and international market volatility, provoked important reduction of industry assets in 1998 in Peru, and in 2002 in Brazil. Additionally, inthe case of Peru, an imprecision in the new tax regulation and the little expectations for devaluation in the exchange rate nuevo sol against U.S. dollar originated significant redemptions between May and December in 2004. In addition, the efficiency (liquidity) of the market was identified as significant for stock, balanced and fixed income funds, in the case ofBrazil. In Peru, the proxy for the knowledge of the industry was significant in the fixed income funds. In Brazil, it was possible to identify some indications of the investors' sophistication in exclusive funds. Ending, the size of the industry in both countries, during the study period, it was represented in a high proportion, by new subscriptions. The last one were significantly influenced by the economic growth, the interest rate, the market volatility, and the regulation.